Nonlinear finite element simulations of ice sheet forces on conical structures - Sand, Björnar; Fransson, Lennart (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2006)
The present paper deals with interaction between an ice sheet and fixed, conical structures. The ice sheet as well as the structure is discretizied by finite elements. The interaction between the ice sheet and the conical structure is simulated using a special contact algorithm which makes it possible to follow the gradually developing contact between the two bodies. As the configuration of the ice sheet under the interaction process changes, the buoyancy forces changes accordingly. This process is traced by introducing a continuous nonlinear foundation model to include the effects of buoyancy forces and specific weight of the ice. The mechanical behavior of ice is approximated using two different constitutive models. In the first case the ice is treated as an isotropic, brittle material, while in the second case the ice is considered being a transversal isotropic and brittle material. When the state of stress at a material point in the ice reaches the failure surface, cracking or crushing is said to occur. After cracking or crushing, the post peak behavior of the ice is approximated as a rigid plastic material. The results from the finite element simulations are compared with analytical methods for calculation of ice sheet forces on conical structures. Godkänd; 2006; Bibliografisk uppgift: CD-ROM. OMAE2006-92470; 20070206 (ysko)